Emergency war plan : the American doomsday machine, 1945-1960 - Maloney, Sean M., 1967- (Potomac Books, an imprint of the University of Nebraska Press, 2021)
Using strategic plans, intelligence analysis, and other materials that have only recently been declassified, Emergency War Plan examines the theory and practice of nuclear deterrence during the 1945-1960 period of the Cold War.